Characterization of 2-((4-(chloromethyl)benzoyl)oxy)benzoate acid for analgesic tablet dosage form formulation - Wuryanto Hadinugroho; Yudy Tjahjono; Kuncoro Foe; Senny Yesery Esar; Caroline Caroline; Maria Annabella Jessica; Hendy Wijaya (Elsevier, 2024)
The 2-((4-(chloromethyl)benzoyl)oxy)benzoic acid (4CH2Cl) is a potential analgesic compound derived from salicylic acid and 4-chloromethyl benzoyl chloride. Characterization required 4CH2Cl for the formulation of tablet dosage forms. This study aims investigate the effect of SSG, PVP-K30, and the combination of SSG*PVP K-30 on the formulation of 4CH2Cl tablets. Additionally, this study aimed to obtain the optimum 4CH2Cl tablet composition. The experiment followed the two-factor simplex lattice design and direct compression method. The analgesic activity of 4CH2Cl in the optimal tablet was investigated using the hot-plate methods. The ANOVA of linear models is acceptable and the polynomial coefficients of quadratic models are similar to those of linear models. The coefficient of the linear model shows that SSG and PVP K-30 increase the Carr index (16.26; 20.61), Hausner ratio (1.19; 1.29), hardness (4.19; 9.39), friability (0.48; 0.67), disintegration time (0.34; 7.50), and drug release (85.29; 97.69). The coefficient of the quadratic model shows that SSG*PVP K-30 increased the Carr index (1.90), Hausner ratio (0.04), hardness (1.88), friability (0.06), and drug release (4.56), and decreased disintegration time (−0.30). SSG and PVP K-30 increased Carr index, Hausner ratio, hardness, friability, disintegration time, and drug release. The combination of SSG*PVP K-30 has the same effect, except that the disintegration time decreased. The optimum tablet formula is 4CH2Cl (300 mg), Ne (75 mg), SSG (33.60 mg), PVP K-30 (22.40 mg), MCC (40 mg), and SDL (up to 800 mg). 4CH2Cl tablets can be a candidate and choice for new analgesic drugs in the future.